Metformin Enhances the Therapy Effects of Anti-IGF-1R mAb Figitumumab to NSCLC - Cao, Hongxin (Sci Rep, 2016)
The insulin-like growth factor (IGF) signaling system plays a critical role in tumorigenesis, highlighting the potential of targeting IGF-1R as an anti-cancer therapy. Although multiple anti-IGF-1R monoclonal antibody (mAb) drugs have been developed, challenges remain in the validation of the therapeutic effects and understanding the molecular mechanism of these mAbs. Herein, we conducted a study to validate the effect of Figitumumab (CP), an anti-IGF-1R mAb, in a panel of non-small cell lung cancer (NSCLC) cell lines. We found all tested cell lines were sensitive to CP, and CP could block IGF-1R and the downstream PI3K/AKT pathway activation. Unexpectedly, we found CP could activate ERK signaling pathway in IGF-1R kinase independent manner, which we further verified was mainly mediated by β-arrestin2. We also investigated the anti-tumor effect of metformin alone as well as its combination with CP to target NSCLC. Metformin could target IGF-1R signaling pathway by attenuating PI3K/AKT and MEK/ERK signaling pathways and down-regulating IGF-1R. Finally, we found that combining metformin with CP could further induce IGF-1R down-regulation and was more effective to target NSCLC cells. Our data suggests the combining of metformin with CP has additive therapeutic value against NSCLC.